Development of motor skills: an application of the micro curricular active learning model/Desarrollo de la motricidad: una aplicación del modelo de aprendizaje microcurricular activo - María Gladys Cóndor Chicaiza; Jannet Del Rocío Cóndor Chicaiza; Susana Paz Viteri; Milton Fernando Romero Obando; Laura Cristina Barba Miranda (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The Physical Education classes developed in this pandemic have generated that teachers look for new teaching alternatives that can be contextualized with virtual resources. The objective of this research is to apply the Active Microcurricular Learning Model of Physical Education in children from 5 to 6 years old, belonging to the first year of General Basic Preparatory Education of a private school in the city of Quito. This proposal was designed to check if it significantly influences the development of gross motor skills. A quasi-experimental design study was carried out with pre and post-test measures without control group, cross-sectional, descriptive, analytical and comparative, in a population formed by 22 children as experimental group, distributed in 11 boys and 11 girls. It was applied in the first half of the 2020-2021 school year, through virtual classes by Zoom; the pretest was carried out in the first week of September and the posttest in the third week of January, with the Mc. Clenaghan and Gallahue battery and the Ozerestky battery of infantile motor skills. It was concluded that there are significant variations in the elements of gross motor skills, such as: running, climbing, crawling and jumping. Statistically, it was demonstrated that the application of this model is effective according to the results obtained and that it is of great importance to develop gross motor skills; in addition, virtual resources can be used in Physical Education classes, empowering them for life in each of their daily activities.